Profile comorbidity and impact of insomnia in the Ibadan (2009)
Background: Little is known about factors that determine the QoL of elderly persons living in developing societies undergoing rapid social changes. Method: A representative sample of elderly Nigerians, aged 65 years and over (n= 2152), was assessed for QoL using the World Health Organization Quality of Life instrument (WHOQoLBref). Other than sociodemographic factors, respondents were also evaluated for major depressive disorder, physical conditions as well as for social network, support and engagement. Using linear regression modeling, these factors were explored for their ability to predict the physical, psychological, social and environmental domains of QoL. Results:Economic status was the most consistent predictor of the four domains of QoL, with the coefficients ranging between 1.0 and 1.68 (p < 0.001 in every instance). Among health variables, functional disability (range: 7.07 – 19.86) and self-rated overall health (range: 7.89 – 18. 42) were the most salient. Participation in community activities (range 7.74 – 17.48) was the most consistent social predictor. As a group, social factors, especially those relating to social support and participation, were the strongest determinants of QoL. Conclusion: Even though health factors are important, social factors, in particular those relating to the quality of social support and participation, are the most important predictors of QoL.